Genetic Architecture of Chile Pepper (Capsicum spp.) QTLome Revealed Using Meta-QTL Analysis - Dennis N. Lozada; Madelin Whelpley; Andrea Acuña-Galindo (Horticulturae, 2021)
In recent years, quantitative trait loci (QTL) mapping approaches have been widely implemented to identify genomic regions affecting variation for different traits for marker-assisted selection (MAS). Meta-QTL analysis for different traits in chile peppers (Capsicum spp.) remains lacking, and therefore it would be necessary to re-evaluate identified QTL for a more precise MAS for genetic improvement. We report the first known meta-QTL analysis for diverse traits in the chile pepper QTLome. A literature survey using 29 published linkage mapping studies identified 766 individual QTL from five different trait classes. A total of 311 QTL were projected into a consensus map. Meta-analysis identified 30 meta-QTL regions distributed across the 12 chromosomes of Capsicum. MQTL5.1 and MQTL5.2 related to Phytophthora capsici fruit and root rot resistance were delimited to < 1.0 cM confidence intervals in chromosome P5. Candidate gene analysis for the P5 meta-QTL revealed functions related to histone methylation and demethylation, indicating the potential role of epigenetics for P. capsici resistance. Allele-specific markers for the meta-QTL will be developed and validated for MAS of P. capsici resistant lines. Altogether, results from meta-QTL analysis for chile pepper QTLome rendered further insights into the genetic architecture of different traits for this valuable horticultural crop.